Astrocytes in fragile X syndrome - Talvio, Karo; Castrén, Maija L. (Frontiers in Cellular Neuroscience, 2024)
Astrocytes have an important role in neuronal maturation and synapse function in the brain. The interplay between astrocytes and neurons is found to be altered in many neurodevelopmental disorders, including fragile X syndrome (FXS) that is the most common inherited cause of intellectual disability and autism spectrum disorder. Transcriptional, functional, and metabolic alterations in Fmr1 knockout mouse astrocytes, human FXS stem cell-derived astrocytes as well as in in vivo models suggest autonomous effects of astrocytes in the neurobiology of FXS. Abnormalities associated with FXS astrocytes include differentiation of central nervous system cell populations, maturation and regulation of synapses, and synaptic glutamate balance. Recently, FXS-specific changes were found more widely in astrocyte functioning, such as regulation of inflammatory pathways and maintenance of lipid homeostasis. Changes of FXS astrocytes impact the brain homeostasis and function both during development and in the adult brain and offer opportunities for novel types of approaches for intervention.